The fundamental principles of Local Agenda 21 - Mohamed Osman, Mariana (IIUM Press, 2017)
Central to this book is the subject of community participation and local governance in Malaysia. It is acknowledged that the community and local authority play an important role in the local decision making process. Stakeholder participation has become an important part of the decision making process related to built environment. It can empower and significantly influence the decision as well as the project design. How effective has participation been historically? Does it actually influence the decision making process in Local Agenda 21 (LA21)? It has been noted that participation practices have increased over the last three decades and is now practised in the planning and development process. However, the constant debates over stakeholder participation and citizen control have not resulted in the ability to identify its real issues and problems. Planning and participation of stakeholder at local level is the process of incorporating into the plan consideration of stakeholder needs, preferences and values attributable to each proposal before the decision making body. The determination of effective planning and decision in LA21 takes into account diverse perspectives and impact allowing the decision makers the opportunity to find solutions and empower stakeholder and local citizen in the LA21 process. This book examines the roles of the stakeholders i.e. community residents, local authority staffs and community organizations in LA21 process in Malaysia. The objectives of this book are to identify the factors influencing the participation of the local authorities in LA21 in Malaysia. Furthermore, the study examines the way in which the participatory principles of LA21 are being carried out in Malaysia and uses a model of public participation to identify the issue of faced among community in the LA21 process.